Procurement Efficiency for Infrastructure Development and Financial Needs Reassessed - Estache, Antonio (World Bank, Washington, DC, 2012)
Infrastructure is the engine for economic growth. The international donor community has spent about 70-100 billion U.S. dollars on infrastructure development in developing countries every year. However, it is arguable whether these financial resources are used efficiently, particularly whether the current infrastructure procurement prices are appropriate. Without doubt a key is competition to curb public procurement costs. This paper analyzes procurement data from multi and bilateral official development projects in three infrastructure sectors: roads, electricity, and water and sanitation. The findings show that the competition effect is underutilized. To take full advantage of competition, at least seven bidders are needed in the road and water sectors, while three may be enough in the power sector. The paper also shows that not only competition, but also auction design, especially lot division, is crucial for reducing unit costs of infrastructure. Based on the estimated efficient unit costs, the annual financial needs are estimated at approximately 360 billion U.S. dollars. By promoting competition, the developing world might be able to save at most 8.2 percent of total infrastructure development costs.